Pros and Cons of Currency Board Arrangements in the Lead-Up to EU Accession and Participation in the Euro Zone - Gulde, Anne (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2000)
Historically, countries with currency board arrangements (CBAs) have experienced lower inflation and higher growth than those with other regimes. The experiences of three candidates for EU membership with CBAs (Estonia, Lithuania, and Bulgaria) have also been generally favorable. Can CBAs serve these transition countries well all the way up to the adoption of the euro? After considering the pros and cons, this paper provides an affirmative answer, but notes that to preserve the viability of their CBAs throughout the process, these countries need to maintain strict policy discipline and be prepared to deal with large capital inflows and asymmetric shocks.